Depression in primary care: Strategies for a psychiatry-scarce environment. (February 2016) - Alson, Amy R; Robinson, Diana M; Ivanova, Danielle; Azer, John; Moreno, Maria; Turk, Marie Lyse; Nitturkar, Abhishek; Blackman, Karen S
More than an algorithm to guide primary care providers through treatment options, integrated care, also called collaborative care, is a validated, systematic, multidisciplinary approach to depression treatment in primary care. Historically, integrated care emerged in response to a mismatch between a growing demand for mental health treatment and scarce mental healthcare resources. Working together, psychiatrists and primary care providers have demonstrated that the principles and tools of chronic disease management improve depression outcomes in primary care. Currently, most antidepressants are prescribed by primary care providers, but with disappointing rates of full, sustained remission. Primary care patients may derive the greatest benefit from existing depression treatment guidelines when they are melded with an approach informed by integrated care principles. This paper will present established guidelines for pharmacologic management of depression as part of a broader framework for depression treatment in the primary care office.